A futuristic view of judicial decisions in its connection with the Human Rights of inmates - Goicochea Elías, José Julio (2021)
We do not discover anything new when we point out that the jurisdictional operators when deciding on the freedom or imprisonment of the defendants are affecting transversal human rights. But let´s stop for a while: the problem is not constituted by norms or principles; how the judges operate on them has become a kind of Russian roulette that directly affects the procedural subjects under their jurisdiction. This lack of proportionality and reasonableness in the criterio they take directly collides with two variables: the predictability of court decisions and legal certainty. Consequently, those affected are the human rights of the inmates. Even more so if we take into account that in our country prison rehabilitation centers resemble Nazi concentration camps.